Analysis of Associations between Health Literacy and Healthy Lifestyle Characteristics among Japanese Outpatients with Lifestyle‐related Disorders. (27th December 2016) - Kudo, Nagako; Yokokawa, Hirohide; Fukuda, Hiroshi; Hisaoka, Teruhiko; Isonuma, Hiroshi; Naito, Toshio
Abstract : Background: The skills of individuals to find and apply adequate information needed to make health decisions have been conceptualized as health literacy (HL). However, limited studies have examined the association between HL and healthy lifestyle characteristics among patients with lifestyle related disorders. Methods: This cross‐sectional study examined associations between HL and healthy lifestyle characteristics among Japanese outpatients with lifestyle related disorders. Participants were 207 men and 254 women who visited Tokorozawa Medical Clinic in Tokorozawa City, Japan, from April to May 2015. Information on five items for functional HL, five items for communicative HL, and four items for critical HL, and healthy lifestyle characteristics was collected by self‐administered questionnaires. Results: Mean age was 68.1 years among men, and 70.3 years among women. In multivariate logistic analysis, a higher HL was significantly associated with having 6–7 healthy lifestyle characteristics among men [Odds ratio (OR) = 2.19, 95% Confidence interval (CI) = 1.09–4.41]. Moreover, functional, communicative, and critical HLs were significantly associated with having 6–7 healthy lifestyle characteristics among men [(OR = 2.34, 95% CI = 1.09–5.02), (OR = 2.37, 95% CI = 1.15–4.88), (OR = 2.78, 95% CI = 1.36–5.70)]. No association was observed between total HL score and healthy lifestyle characteristics among women. Conclusion: Our study revealed a positive association between HL and healthy lifestyle characteristics among male outpatients with lifestyle related disorders, suggesting that men, but not women, are likely to engage in health‐promoting behaviors based on several aspects of HL. Further studies will be needed to confirm this gender discrepancy.